2023
DOI: 10.3389/fpsyg.2023.1071615
|View full text |Cite
|
Sign up to set email alerts
|

The influence of physical exercise on college students’ life satisfaction: The chain mediating role of self-control and psychological distress

Abstract: ObjectiveTo explore the relationship between physical exercise and life satisfaction among college students and test the dual mediating role of self-control and psychological distress between them.MethodsA sample of 526 Chinese college students completed questionnaires regarding physical exercise, life satisfaction, self-control and psychological distress, of which 38.4% were boys.ResultsPath analyzes indicated that physical exercise was positively correlated with life satisfaction, and this link could be medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…This explanation aligns with prior research findings as well. First of all, previous research have shown that physical exercise does not directly impact life satisfaction but can enhance it indirectly through improved self-control, mental health, and social support ( Dai and Yao, 2012 ; Zhou et al, 2023 ). According to Zhou et al (2023) , engaging in physical exercise can improve self-control, leading to a reduction in psychological distress and an increase in life satisfaction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This explanation aligns with prior research findings as well. First of all, previous research have shown that physical exercise does not directly impact life satisfaction but can enhance it indirectly through improved self-control, mental health, and social support ( Dai and Yao, 2012 ; Zhou et al, 2023 ). According to Zhou et al (2023) , engaging in physical exercise can improve self-control, leading to a reduction in psychological distress and an increase in life satisfaction.…”
Section: Discussionmentioning
confidence: 99%
“…First of all, previous research have shown that physical exercise does not directly impact life satisfaction but can enhance it indirectly through improved self-control, mental health, and social support ( Dai and Yao, 2012 ; Zhou et al, 2023 ). According to Zhou et al (2023) , engaging in physical exercise can improve self-control, leading to a reduction in psychological distress and an increase in life satisfaction. Engaging in physical exercise can also enhance one’s self-efficacy and perceived social support, ultimately leading to greater individual satisfaction with life ( Dai and Yao, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…Currently, there is significant interest in understanding the relationship between physical activity and life satisfaction among university students. Previous studies suggested a positive association between physical activity and life satisfaction [26,27]. Furthermore, physical activity was found to have positive effects on mood, anxiety, and depression [28,29].…”
Section: Theoretical Foundations Of Researchmentioning
confidence: 91%
“…Currently, there is signi cant interest in understanding the relationship between physical activity and life satisfaction among university students. Previous studies have suggested a positive association between physical activity and life satisfaction [16] [17] . Furthermore, physical activity has been found to have positive effects on mood, anxiety, and depression [18][19] [20] .…”
Section: Theoretical Foundations Of Researchmentioning
confidence: 99%